2019
DOI: 10.1088/1757-899x/537/3/032051
|View full text |Cite
|
Sign up to set email alerts
|

Field-work automation of hydrocarbon exploration using a passive seismic-electric method

Abstract: The paper proposes to exclude the active source of the seismic field from the measurement scheme, which is often a massive truck with equipment installed on it, which in its turn makes it difficult and increases the cost of field-work. The proposed passive measurement installation allows the detection of hydrocarbon deposits by registering the natural fields of the Earth. All measurements can be carried out by one person due to the use of magnetic antennas. A method of field measurements by means of such insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…As shown in Table 2 , obtained in 2019–2020, the experimental data confirmed the results of the measurements in 2014–2018 [ 27 , 28 , 44 , 45 , 46 , 47 ]. Figure 9 b also shows a curve obtained by solving Equations (1)–(8), according to which the values of the electric field strength E will correspond to the magnitude of the observed SE effect on the day surface.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…As shown in Table 2 , obtained in 2019–2020, the experimental data confirmed the results of the measurements in 2014–2018 [ 27 , 28 , 44 , 45 , 46 , 47 ]. Figure 9 b also shows a curve obtained by solving Equations (1)–(8), according to which the values of the electric field strength E will correspond to the magnitude of the observed SE effect on the day surface.…”
Section: Resultssupporting
confidence: 84%
“…This was the first attempt to process data obtained in different years of observation. Based on the experience of [ 27 , 28 , 44 , 45 , 46 , 47 ] on this profile, it can be concluded that the amplitude value of the observed cross-correlation coefficient on the Earth’s surface depends on many factors. Thus, the absolute value of this coefficient cannot be used for the assessment, and, therefore, the shape of the resulting curve is a more important factor.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation